A Protective Layer for Lithium Metal Anode: Why and How. Issue 4 (31st January 2021) - Han, Zhiyuan; Zhang, Chen; Lin, Qiaowei; Zhang, Yunbo; Deng, Yaqian; Han, Junwei; Wu, Dingcai; Kang, Feiyu; Yang, Quan‐Hong; Lv, Wei
Abstract: Lithium metal is the most promising candidate anode material for high energy density batteries, but its high activity and severe dendrite growth lead to safety concerns and limit its practical use. Constructing a protective layer (PL) on the lithium surface to avoid the side reactions and stabilize the electrode‐electrolyte interface is an effective approach to solve these problems. In this review, the recent progress on PLs is summarized, and their desired properties and design principles are discussed from the aspects of materials selection and the corresponding fabrication methods. Advanced PLs with different properties are then highlighted, including a self‐adjusting feature to increase structural integrity, the synergistic effect of organic and inorganic hybrids to improve mechanical properties and ionic conductivity, the use of embedded groups and ion diffusion channels to regulate ion distribution and flux, and a protective barrier to suppress corrosion from humid air or water. Finally, the remaining challenges and the possible solutions for PL design in future studies are proposed. Abstract : In this review, advanced protective layers with different functions to stabilize lithium metal anodes are discussed from the aspects of fabrication methods, material selections, and structure‐function relationships. The remaining challenges and future perspectives are also proposed, which can help promote the practical applications of lithium metal anode in high energy density batteries in the future.